Dynamic Assembly of Small Parts in Vortex-Vortex Traps Established within a Rotating Fluid - Lee, Taehoon (Advanced materials (Deerfield Beach, Fla.), 2019)
© 2019 WILEY-VCH Verlag GmbH & Co. KGaA, Weinheim.